Determinant Factors Affect Neurophaty in Diabetic Patient - Frisca, Sanny; Koerniawan, Dheni (Indonesian Journal of Global Health Research, 2024)
Hyperglycemia conditions will result complications in patients both for cardiovascular and neurological system. The incidence of neuropathy and peripheral arterial disease (PAD) are two things that increase mortality. Loss of protective sensation will reduce the patient's awareness of ulcers so that patients do not receive treatment early. Meanwhile, PAD conditions increase the incidence of ischemia in the distal area, especially in the legs, resulting ulcer. This research aims to look at the factors that contribute to these two conditions. Data collected to 40 respondents with the inclusion criteria who are DM patients which never had an amputation, the relationship and contribution of factors to neuropathy and PAD (were measured by sensation points on sole by monofilament and dorsalis pedis artery palpation) and analyzed with ordinal regression. The results of the study showed that none of the respondents experienced PAD so that bivariate tests could not be carried out. Meanwhile, the results of the bivariate test for neuropathy showed that 3 factors were significantly related to gender (p=0.038), duration of illness from DM (p=0.05), and foot condition (p=0.003). It is found from ordinal regression that foot condition (β= 1.237; p= 0.028; OR= 1.237) has significant effect to neuropathy.